ANALISIS SPASIAL PENYERANGAN HAMA TIKUS SAWAH PADA TANAMAN PADI DI NAGARI TIMBULUN - Afifa, Nurma; Prarikeslan, widya (JURNAL BUANA, 2025)
Field mice or Rattus argentiventer are dangerous rodent pests. These mice attack rice plants starting when the rice stalks are still young until the rice is harvested. A single rat can damage between 11-176 stalks of rice per night. By mapping the distribution of damage, the home range and looking for the relationship between the ecological landscape of rice fields and the community's five farming businesses, the level of danger of this pest can be estimated. The methods used are Kernel density, Overlay and questionnaire distribution. Based on the results of processing using GIS, it was found that the distribution of rat pests in Nagari Timbulun was 188 points, the range covered 221.76 ha of land and the most influential landscape was the high embankment with the discovery of 166 damage points. Apart from that, the highest five farming indicators are the selection of superior seeds and soil processing with an achievement percentage of 100%. Meanwhile, the lowest indicator is the pest and disease control indicator with an achievement percentage of 38.02%.